2007
DOI: 10.1152/jn.01138.2006
|View full text |Cite
|
Sign up to set email alerts
|

Different Neural Adjustments Improve Endpoint Accuracy With Practice in Young and Old Adults

Abstract: The purpose of the study was to determine the practice-induced adjustments in the motor-output variability and the agonist-antagonist activity that accompanied improvements in endpoint accuracy of goal-directed isometric contractions in young and old adults. Young and old adults performed 100 trials that involved accurately matching the peak of a force trajectory (25% maximum) to a target force in 150 ms. Endpoint accuracy was quantified as the absolute difference between the target and the peak force and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 54 publications
4
79
3
6
Order By: Relevance
“…Lengthening contractions exhibit greater motor unit synchronization than shortening contractions (Semmler 2002), which strongly indicates an altered frequency modulation of the motor neuron pool (Christou et al 2007). Our findings provide similar evidence and demonstrate that the frequency modulation of motor units differs for force release and force increase.…”
Section: Phase and Force Variabilitysupporting
confidence: 79%
“…Lengthening contractions exhibit greater motor unit synchronization than shortening contractions (Semmler 2002), which strongly indicates an altered frequency modulation of the motor neuron pool (Christou et al 2007). Our findings provide similar evidence and demonstrate that the frequency modulation of motor units differs for force release and force increase.…”
Section: Phase and Force Variabilitysupporting
confidence: 79%
“…A practice effect might have also contributed to the lack of an age-related difference in the SD of foot acceleration as subjects practiced the tasks until they could achieve the target speed; old adults practiced more than young adults did in the current study and in the one by Christou et al (2003). Increased practice has been shown to reduce kinematic variability and likely contributed to similar SDs of foot acceleration for young and old adults (Christou et al 2007;Hortobagyi et al 2001;Keen et al 1994;Kornatz et al 2005;Tracy and Enoka 2006).…”
Section: Kinematicsmentioning
confidence: 73%
“…The adaptations responsible for the declines in performance often exhibited by older adults include the loss of muscle mass associated with sarcopenia (Dey et al 2009;Forrest et al 2007;Goodpaster et al 2006;Narici and Maffiuli 2010) and an increase in motoroutput variability (Christou et al 2007;Ofori et al 2010;Sosnoff and Voudrie 2009;Vaillancourt et al 2004). Although the consequences of sarcopenia and a worsening of motor-output variability are typically observed concurrently (Barry et al 2007;Carville et al 2007;Christou and Carlton 2002c;Christou et al 2003;Graves et al 2000;Seynnes et al 2005;Tracy and Enoka 2002;Tracy et al 2007), it is possible for one adaptation to appear without the other.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of motor units in agonist muscles, for example, can differ between young and older adults and contribute to greater trajectory variability (Kornatz et al 2005;Laidlaw et al 2000) and impairments in force control (Vaillancourt et al 2003) in older adults. The accuracy of targeted movements can also be influenced by the synergistic activation of antagonistic muscles (Berardelli et al 1996;Christou et al 2007;Corcos et al 1989;Ghez and Gordon 1987;Gottlieb et al 1992), and the increased coactivation often observed in older adults (Darling et al 1989;Seidler-Dobrin et al 1998) can impair movement accuracy.…”
Section: Introductionmentioning
confidence: 99%